2016
DOI: 10.1038/srep31688
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic characterization of the water vapor-salt interfacial layer reveals a unique biphasic adsorption process

Abstract: Our quantitative understanding of water adsorption onto salt surfaces under ambient conditions is presently quite poor owing to the difficulties in directly characterizing this interfacial layer under these conditions. Here we determine the thickness of the interfacial layer on NaCl at different relative humidities (RH) based on a novel application of atomic force spectroscopy and capillary condensation theory. In particular, we take advantage of the microsecond-timescale of the capillary condensation process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…After the advent of AFM, topography images of NaCl, KBr, and other alkali halide surfaces were obtained in controlled RH conditions. Some of these studies reported the movement of the steps on NaCl to start at around 40–45% RH at RT and associated it with the formation of the liquid solvation layer (also called hydration layer for water) on the surface, in agreement with the transition from the first domain to the second domain found in ref and with infrared spectroscopy measurements in ref . The surface properties such as contact potential and friction coefficient change upon the formation of this liquid layer. , On a more recent study, it was claimed that no dissolution of ions takes place below 30% RH . For KBr, this transition was reported around 55% HR, and both the moving steps and the formation of the hydration layer were observed above this threshold. , In another recent study, large defects created by poking the KBr surface with an AFM tip were investigated .…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…After the advent of AFM, topography images of NaCl, KBr, and other alkali halide surfaces were obtained in controlled RH conditions. Some of these studies reported the movement of the steps on NaCl to start at around 40–45% RH at RT and associated it with the formation of the liquid solvation layer (also called hydration layer for water) on the surface, in agreement with the transition from the first domain to the second domain found in ref and with infrared spectroscopy measurements in ref . The surface properties such as contact potential and friction coefficient change upon the formation of this liquid layer. , On a more recent study, it was claimed that no dissolution of ions takes place below 30% RH . For KBr, this transition was reported around 55% HR, and both the moving steps and the formation of the hydration layer were observed above this threshold. , In another recent study, large defects created by poking the KBr surface with an AFM tip were investigated .…”
Section: Introductionsupporting
confidence: 75%
“… 16 , 17 On a more recent study, it was claimed that no dissolution of ions takes place below 30% RH. 20 For KBr, this transition was reported around 55% HR, 11 and both the moving steps and the formation of the hydration layer were observed above this threshold. 16 , 21 In another recent study, large defects created by poking the KBr surface with an AFM tip were investigated.…”
Section: Introductionmentioning
confidence: 94%
“…The adsorption of water on the cleavage face of various alkali halides (NaCl, KCl, KBr, KI) has been also studied as a function of humidity. It was found that a characteristic relative humidity value (CRH) exist that separates two water adsorption regimes identified by their strong differences in surface ionic conductivity [78,79] (Fig. 12a).…”
Section: Water On Saltsmentioning
confidence: 99%
“…12,13 The adsorption of water on solid surfaces is of general interest from both fundamental and applied perspectives but the adsorption of water on nonoxide ionic substrates is not well understood, although some investigations have been carried out on NaCl. 18 The reported CaF 2 adsorbents usually have relatively low Brunauer−Emmett−Teller (BET) surface areas, generally lower than 35 m 2 g −1 , resulting in low wateradsorption capacities. 11 In addition, the effects of the surface area and morphology of CaF 2 on water-adsorption properties have not been systematically investigated yet.…”
Section: ■ Introductionmentioning
confidence: 99%